Post‐operative arterio‐venous fistula blood flow influences primary and secondary patency following access surgery. Issue 3 (9th March 2018) - Benaragama, Kapila S.; Barwell, Jennifer; Lord, Chris; John, Biku J.; Babber, Adarsh; Sandoval, Shella; Lindsey, Ben; Fernando, Bimbi
SUMMARY: Purpose: Primary arteriovenous fistula arterio venous fistula (AVF) formation has proven to be the best and optimal vascular access for the majority of haemodialysis patients. At present there are limited data to suggest which haemodynamic parameters most correlate with the likelihood of early failure. The aim of this study is to identify the haemodynamic predictors of early failure, hence identify which fistulae may benefit from timely pre‐emptive intervention. Material and Methods: Retrospective analysis of data was performed of 201 patients undergoing native AVF creation over a one year period. Demographic details, co‐morbidity, preoperative vessel calibre were collected. Flow was measured by duplex ultrasound post operatively. Results: Preoperative vein calibre (p = 0.01) and fistula flow (p < 0.001) positively affected primary patency. Age, gender, ethnicity, type of fistula, hypertension and preoperative arterial calibre did not influence outcome. Regression analysis showed that the strength of correlation between early postoperative fistula flow and patency decreased progressively with time. Six week flow predicts early, but not late, failure. ROC analysis identified 300 ml/min flow as the best predictor of patency. Fistulae with flow above 300 ml/min were more likely to remain patent over the next 12 months (p < 0.001, HR = 7.4). Conclusion: Postoperative fistula flow of less than 300 ml/min identifies AVFs at high risk of early failure. These may be candidates for early intervention with balloon assisted maturation. The findings of this retrospective cohort study strongly support the need for a more robust prospectively designed trial identifying haemodynamic factors that can predict mid and long‐term AVF patency.